Pengaruh Pendapatan Usaha Koperasi Terhadap Sisa Hasil Usaha pada Koperasi Bina Artha Ventura Tasikmalaya - Sholiha Kurniavie; Usep Riyadi (LPPM POLITEKNIK LP3I BANDUNG, 2019)
This study was conducted to determine the influence of cooperative business income to business revenue at Bina Artha Ventura Tasikmalaya Cooperation. The method used in this study is correlational and descriptive method. The population of this study is the totality of all that is possible, the results of counting or measurement, quantitative and qualitative data about the particular characteristics of several years of cooperative business income collection completely and obviously that want to learn its characteristics. The writer took some of the revenues that is cooperative business income and operating revenues from 2014 to 2018 as research sample. In collecting the data, the writer conducted observation, interviews and documentation on the research object. After the data is collected, then the data is analyzed using product moment correlation coefficient, f-test, the coefficient of determination and t-test with a level (α) 5%. From the results, it is obtained by the correlation coefficient (r) = 0,819 with interpretation of